Introduction to the Theoretical Analysis of Social Exclusion of Public Transport in Rural Areas - József Pál Lieszkovszky (DETUROPE, 2018)
Western societies are facing the same problems worldwide regarding the provision of public transport services in rural, sparsely populated and peripheral areas. One of the main reasons is that due to the increasing number of cars (which can satisfy the mobility needs much better), the number of passengers of public transport services are steadily decreasing (ITF, 2015). However, we do not forget that supplying these areas with public transportation have in fact always been problematic: the dispersed settlement network is a given fact as well as the low population density that never generated high demand (Ambrosino, Nelson & Romanazzo, 2003). Passengers of public transport in rural areas are not classified by the majority of international literature as voluntary travellers on public transport vehicles, but who belong to those groups which stand in need of travelling by them. Regarding this issue, the major starting-point is the ability to have access to car which can be modified by other factors (financial situation, sex, age, physical condition, type of household, foreign language skills etc.). Those people who have limited or no access to car are thus constrained by the schedule of public transport vehicles and depend on its reliability or even no access to any transport mode belongs to the group of transport deprived. The purpose of this article is twofold: to introduce those groups who are suffering from the decline of public transport in rural areas and to highlight the necessity of these researches in Central and Eastern Europe.